Astrocyte–leucocyte interactions and the mechanisms regulating matrix degradation in CNS tuberculosis. (20th July 2007) - Green, J.A.; Friedland, J.S.
Abstract : The CNS (central nervous system) has a unique pattern of immune response to infection. TB (tuberculosis) of the CNS is devastating with widespread tissue destruction. In TB, astrocyte–leucocyte interactions are key in regulating MMP (matrix metalloproteinase) activity and are regulated by complex signalling pathways. A synergistic interaction between interferon γ and monocyte-derived mediators drives high-level astrocyte MMP-9 secretion; this and other networking effects are inhibited by steroids. Better understanding of regulatory mechanisms may identify potential switch points that could be future therapeutic targets.